Allelopathic effect of Cyperus iria towards aerobic rice (MRIA 1) / Nur Anis Sabireen Lazim - Lazim, Nur Anis Sabireen (2019)
Aerobic rice is as a staple food that consumed daily by the people. Aerobic rice was produced through crossing technique in between the traditional upland, which is drought tolerance and improved lowland, which is high yield. Glasshouse study in Randomized Complete Block Design (RCBD) was conducted at Greenhouse University Technology MARA (UiTM) Jasin. This experiment was carried out to identify and characterized weed population growth with different concentration of Cyperus iria and to analyze aerobic rice growth performance (plant height, number of tiller and chlorophyll content) upon application of different concentration of Cyperus iria which are 20gram, 30gram and 40gram. Fimbristylis miliacea, was found as dominant weed species in all treatments followed by Sphenoclea zeylanica. The highest plant height at wf30 which is 83.77cm and the lowest at wf40 which is 71.03cm. Besides that, plant heights, number of tillers and chlorophyll contents for variety MRIA 1 are not affected by different concentration of Cyperus iria.